Preserving Betawi Culture: Introducing Additive Manufacturing for Ondel-Ondel Souvenirs in Micro, Small, and Medium Enterprises (MSMEs/UMKM) - Saptaji, Kushendarsyah; Ifat, Ifat; Putra, Indra Pertama; Kalam, Ikramin; Islam, Sri Susilawati; Triawan, Farid; Siswojo, Nathanael Ansel; Lubis, Steven Abed Daniel; Bryan, Jonathan; Handani, Nadya Geraldine (Center for Research and Community Service of Sampoerna University, 2024)
The contributions of campus as a technology hub to the society need to be increased. One of the way is to help micro, small, and medium enterprises (MSMEs) or Usaha Mikro, Kecil, dan Menengah (UMKM) to improve their process, capability and product. In this study, a team consisted of students and lecturers from Faculty of Engineering and Technology Sampoerna University led a community service project on one of MSMEs in Jakarta area. Over eight months, the team introduced innovative manufacturing techniques like 3D printing and mold-making to one of the MSMEs called Jawara Peci. Jawara Peci sells traditional souvenir, Ondel-ondel miniature. The purpose of this activity is to help Jawara Peci to have a unique ondel-ondel miniature product with the use of technology in order to preserve the cultural heritage of Betawi. The activity includes, socialization and introduction of the program, 3D design and product development, prototyping and delivery. The activity was successfully producing a new method to produce an Ondel-ondel souvenir using 3D printing and casting. The proposed method is expected can be implemented by the Jawara Peci to improve the uniqueness of the Ondel-ondel souvenir so that can contribute to economic growth and cultural awareness. This activity highlighted the potential of merging technology and heritage in improving inclusive economic development.